Orphan regulations for orphan drug development in India - Reddy, D. Saikiran; Pramodkumar, T. M.; Reddy, Yugendar; Sirisha, K. (Asian Journal of Pharmaceutics (AJP), 2014)
Through this review article an attempt has been made to put forward the challenges faced by rare disease drug development and the current scenario of orphan drug legislations in India. An orphan drug is a pharmaceutical agent that is used to treat a rare medical condition (viz., glioblastoma multiforme, nocardiosis, Tourette syndrome, etc). Developed countries such as United States (US), Europe, Japan, and Australia have laid down legal framework for combating rare diseases. A path breaking legislation was formulated by the US government way back in 1983, known as â€œOrphan Drugs Act (ODA).â€ The key purpose of ODA was to incentivize R and D initiatives for such drugs to treat millions of population suffering from â€œorphan diseases.â€ Though the percentage of patients suffering from â€œrare diseasesâ€ in India is reportedly higher than the world average, unfortunately even today such cases get little help from our government. Indian government should also encourage its domestic pharmaceutical industry to get engaged in research for orphan drugs by putting an â€œODAâ€ in place and extending financial support, and regulatory concessions like smaller and shorter clinical trials, without further delay. Thus, India could wellâ€‘demonstrate that the concept of orphan drugs for orphan diseases is really not orphan in India. Key words: Orphan diseases, orphan drugs act, orphan drug